Proceedings of the 15th International Conference on Ground Penetrating Radar 2014
DOI: 10.1109/icgpr.2014.6970406
|View full text |Cite
|
Sign up to set email alerts
|

Maxwell-wagner-sillars, adsorbed water, and free-water dielectric relaxations within a hydrated arid-zone calcic soil

Abstract: Abstract-We measured the broadband (40 Hz-20 GHz) rel ative dielectric permittivity of sieved surficial samples of an arid-zone soil. The soil samples were equilibrated at 25°C with relative humidities of 43, 54, 84, and 97 %. Debye-like Maxwell-Wagner-Sillars (MWS) polarization relaxation times of 309, 227, and 73 ns were calculated for the soil samples equili brated at relative humidities of 43, 54, and 84 %, respectively.Due to electrode polarization, MWS polarization relaxations could be not be discerne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…reaching 14.33 MHz at 15.4 % for the quartz-calcite soil and 35.52 MHz at 17.0% for the quartz gypsum soil. This trend is consistent with general theory of MWR, such as formulated by Matzler [19 ] for a spherical conductive inclusion whereby ire1 is expressed as (10) in which 0"2 is the real conductivity of an inclusion, &1 ' is the real part of &1 * of the host medium, and &2 ' is that of the inclusion. Equation (1) differs little fromfrel = 1/2nT, where the relaxation time T = CT!…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…reaching 14.33 MHz at 15.4 % for the quartz-calcite soil and 35.52 MHz at 17.0% for the quartz gypsum soil. This trend is consistent with general theory of MWR, such as formulated by Matzler [19 ] for a spherical conductive inclusion whereby ire1 is expressed as (10) in which 0"2 is the real conductivity of an inclusion, &1 ' is the real part of &1 * of the host medium, and &2 ' is that of the inclusion. Equation (1) differs little fromfrel = 1/2nT, where the relaxation time T = CT!…”
Section: Discussionsupporting
confidence: 90%
“…We used a least squares matching approach to minimize the errors for .0' and .0". Our companion paper [10] tests of one of these soils at low water contents and conductivities, and with less EP, by combining open-ended coaxial and low frequency impedance methods. The results greatly improve our previous results [3] over a far wider frequency range, and require no modeling to identify the relaxation frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Gas and water were dispersed in the skeleton of unsaturated soil. Part of the water adsorbed by the soil skeleton equated to the residual water content, whereas and remaining part existed in the form of flowing water (Grant et al, 2014). The monitoring results showed that soil volumetric water content always exceeded the residual water content.…”
Section: Discussionmentioning
confidence: 99%